2011
DOI: 10.1111/j.1540-8159.2011.03223.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter‐Defibrillator Recipient Attitudes towards Device Deactivation: How Much do Patients Want to Know?

Abstract: Patients with ICDs are routinely counseled about the benefits of ICDs, but options for device deactivation are not well understood by patients. Most patients would like to be involved in deactivation decisions and we feel this should be discussed well in advance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…Similarly, the informed consent process tends to concentrate on peri‐procedural and short‐term risk rather than considering events, sometimes perceived as hypothetical, later in the course of life. Evidence suggests that patients and families sometimes anticipate later adverse clinical scenarios and show a willingness to confront these issues at the time of implantation 30, 31. Guidelines issued by the European Heart Rhythm Association suggest that end‐of‐life issues should be incorporated in pre‐implant discussions and revisited at intervals along the heart failure disease trajectory 32.…”
Section: Implanted Electronic and Mechanical Assist Devicesmentioning
confidence: 99%
“…Similarly, the informed consent process tends to concentrate on peri‐procedural and short‐term risk rather than considering events, sometimes perceived as hypothetical, later in the course of life. Evidence suggests that patients and families sometimes anticipate later adverse clinical scenarios and show a willingness to confront these issues at the time of implantation 30, 31. Guidelines issued by the European Heart Rhythm Association suggest that end‐of‐life issues should be incorporated in pre‐implant discussions and revisited at intervals along the heart failure disease trajectory 32.…”
Section: Implanted Electronic and Mechanical Assist Devicesmentioning
confidence: 99%
“…To prevent shocks at the end of life that do not meaningfully prolong survival, a recent Heart Rhythm Society consensus statement recommended proactive communication with patients regarding deactivation 3 . However, most surveys have found that the majority of ICD patients would not consider deactivation in even in deleterious future health states including terminal cancer 4 , constant dyspnea 5 , or receipt of frequent shocks 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…141 In fact, most patients are not even aware that deactivation of the shocking function is an option, and a large number of ICD recipients indicate they would keep the ICD on even if dying of cancer or receiving daily shocks. 19,141,147 Interviews with electrophysiologists, cardiologists, internists, and geriatricians demonstrate that although all physicians believe they should take an active role in these conversations, they admit they rarely do. 148 In terms of management of devices in hospice, a recent nationwide study of hospices showed that 44% reported that at least 1 patient had been shocked by the ICD in the last year, and only 10% of hospices reported having a written policy that addressed deactivation (that is, a policy that encouraged discussion, not a policy that required deactivation).…”
Section: End-of-life Considerations and The Icdmentioning
confidence: 99%